LINEAR AND NONLINEAR TECTONICS IN EARTH HISTORY AND THEIR CAUSES - Patalakha Ye.I.; Markov M.S. (My University, 1989)
The linear fold tectonics that determines the structural look of the continental crust expresses a P-T regime of the crust that assumes the presence of a thick 'load-bearing' mesozonal layer (with a temperature range of 100-600° C) in its section, whose rheological properties allow the development of planetary fault zones, expressed on geological maps as long linear fold belts. This regime predominated through almost the entire Neogaean. This is particularly evident in the case of Paleozoide folded belts, in which the mesozone consists almost entirely of the Riphaean-Paleozonic geosynclinal folded complex and in part of ancient blocks of the catazone of the early Precambrian stage that underwent linearization under the new conditions. The situation was somewhat different in Mesozoide and Alpide setting: here the epizonal geosynclinal folded complex is everywhere underlain by a thick mesozone. The epizone complexes are rather passively deformed, so that the linearity of their structure was largely dictated by the presence of the underlying mesozone. In an earlier stage of evolution, heating of the continental crust was so great that the mesozone (like the epizone) was much too thin; therefore the rheological behavior of the crust was almost entirely governed by an anomalous low-viscosity (granitized) catazone. Thus, the layered complexes of the continental crust were given their linear tectonics primarily by the mesozone, through suture folding, as this is the only type of deformation structure that was rheologically possible in it.
Keywords: Precambrian; Precambrian; Докембрий